SINTESIS SILIKA GEL TERIMOBILISASI DIFENILKARBAZON DARI ABU SEKAM PADI MELALUI TEKNIK SOL GEL - Ni Nyoman Sri Nopianingsih; I Wayan Sudiarta; Wahyu Dwijani Sulihingtyas (Jurnal Kimia (Journal of Chemistry), 2015)
A research on synthesis diphenylcarbazone immobilized silica gel from rice husk ash by sol-gel technique has been conducted. The purpose of this research was to synthesize the diphenylcarbazone immobilized silica gel from rice husk ash by sol-gel technique.  This research included modification of silica gel of rice husk ash and silica gel characterization by IR spectra and X-RD. The results showed that the diphenylcarbazone immobilized silica gel has been successfully synthesized. It can be seen from the FTIR spectrum that silica-imobilized revealed peaks at wave numbers of ±1087.85cm-1 indicating the presence of Si-O-Si. The peak seen at wave numbers of  ±952.84cm-1 indicating the presence of Si-O, at ±3361.93cm-1due to the Si-OH bond which was the main functional group  of silica gel. Another peaks at ±3313.71cm-1, ±800.46cm-1, ±1602.85cm-1,±1700 cm-1, and ±1602.85cm-1 suggesting the presence of N-H, aromatic C-H (substituted benzene), aromatic C=C, N=N and C=O stretching. X-RD data showed that the structure of diphenilcarbazone immobilized silica gel was amorphous.